New changes in pregnancy and lactation labelling: Review of dermatologic drugs - Yun Pei Koh, MBBS; Elizabeth A. Tian, BSc (Pharmacy); Hazel H. Oon, MD, MRCP (UK) (Wolters Kluwer, 2019)
Background: The U.S. Food and Drug Administration has published new pregnancy and lactation labelling rules that set standards on the presentation of information with regard to drug usage during pregnancy and breastfeeding, as well as the effects on fertility. These guidelines became effective June 30, 2015, and classified the risks of using prescription drugs during pregnancy in three detailed subsections: Pregnancy, Lactation, and Females and Males of Reproductive Potential. These sections describe the risks within a real-world context of caring for these patients. Objective: In this study, we reclassified and categorized drugs and treatments commonly used in dermatology according to these new guidelines. Methods: We performed a search of the medical literature about the use of relevant prescription drugs during pregnancy and breastfeeding and their effect on fertility. The search included prospective and retrospective studies, review articles from PubMed-indexed journals (from inception to November 2018), U.S. Food and Drug Administration records, pregnancy exposure registries, relevant information and studies provided in drug labeling by companies, and updated pharmacologic texts and guidelines up to 2018. Results: Topical immunomodulators, systemic immunomodulators (including biologics), systemic antipruritic agents, antimicrobials, as well as acne, hair, and cosmetic agents were included. We have made best attempts to review and consolidate existing and new data and include them in our guide. Conclusion: This new narrative format facilitates prescribing by considering a variety of factors. One previously overlooked aspect was the impact on the reproductive potential of both male and female patients. Rather than depending on overly simplistic letter risk categories, dermatologists will now need to make prescribing decisions based on each patient and the information provided, which will allow for better decision making and patient care.